1976
DOI: 10.1093/ajcn/29.6.600
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sweat nitrogen losses in evaluating protein utilization by preadolescent children

Abstract: A nitrogen balance study was conducted to determine the effects of three levels of nitrogen intake on the loss of nitrogen through sweat and to assess further the impact of sweat nitrogen on protein needs of preadolescent children. Values were determined through the collection of 24-hr, total body sweat samples from twelve healthy boys having a mean age of 8 years, 8 months. Mean height and weight of the subjects were 131.4 cm and 31.0 kg, respectively. Environmental conditions were relatively constant during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…As shown in Figure 1, dermal losses differed significantly depending on the climate under which the study was conducted; therefore, we analyzed the data from the 2 climatic regions separately. A summary of the average dermal and miscellaneous nitrogen losses obtained in each study [excluding those individual data points reported by Calloway et al (86) Because it has often been reported that dermal nitrogen losses are directly related to nitrogen intake (45,86,88,91,92), we alternatively used analysis of covariance to estimate separate regression equations for the response of dermal (plus miscellaneous) nitrogen losses as a function of nitrogen intake within each of the 2 climatic regions. We found a significant (P = 0.006) response curve for the temperate studies only: On the basis of these analyses, we adjusted the nitrogen balance data for each study by 1) the measured dermal losses, if available (with the use of additional 1.77 mg N for miscellaneous…”
Section: Dermal and Miscellaneous Nitrogen Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, dermal losses differed significantly depending on the climate under which the study was conducted; therefore, we analyzed the data from the 2 climatic regions separately. A summary of the average dermal and miscellaneous nitrogen losses obtained in each study [excluding those individual data points reported by Calloway et al (86) Because it has often been reported that dermal nitrogen losses are directly related to nitrogen intake (45,86,88,91,92), we alternatively used analysis of covariance to estimate separate regression equations for the response of dermal (plus miscellaneous) nitrogen losses as a function of nitrogen intake within each of the 2 climatic regions. We found a significant (P = 0.006) response curve for the temperate studies only: On the basis of these analyses, we adjusted the nitrogen balance data for each study by 1) the measured dermal losses, if available (with the use of additional 1.77 mg N for miscellaneous…”
Section: Dermal and Miscellaneous Nitrogen Lossesmentioning
confidence: 99%
“…Millward and Roberts (8), in their review of the literature, concluded that a value of ≤ 5 mg N • kg Ϫ1 • d Ϫ1 would be more appropriate. Studies in infants (103) and preadolescent children (91,92) suggest that dermal or sweat nitrogen losses are Ϸ10 mg • kg Ϫ1 • d Ϫ1 , or more, and that they vary with the nitrogen intake (91,92,104). Because the rate of nitrogen loss via the skin varies significantly, as does body surface area, we chose to use only data from adults to estimate a suitable allowance for dermal and miscellaneous losses.…”
Section: Dermal and Miscellaneous Nitrogen Lossesmentioning
confidence: 99%
“…This was the mean value obtained by multiple nitrogen balance studies on growing subjects, including children and adolescents (34)(35)(36)(37)(38)(39)(40). Regarding miscellaneous nitrogen losses other than that in feces and urine, the value of 6.562.3 mgN/kg body weight/d (range, 5-9 mgN/kg body weight/d) obtained in current reports (34,(41)(42)(43)(44), was adopted. The same value adopted for the protein maintenance requirement was used in all age groups composed of growing subjects, since there was no evidence to suggest any differences among these age groups.…”
Section: Rda (G/d) Was Considered As Being Equal To the Ear (G/d)3thementioning
confidence: 61%